Profile of Pattern Generalization Strategies in Functional Thinking of Middle School Students - Adinda, Anita; Nst, Ammi Thoibah; Nst, Sarah Auliyah (Jurnal Paedagogy, 2025)
This study aims to describe the profile of pattern generalization strategy (SGP) in functional thinking of secondary school students. The profile of SGP in functional thinking of secondary school students in this study is a differentiator in revealing students’ pattern generalization strategies in functional thinking in more detail. A qualitative approach was used in this study. Data collection was conducted on 220 students of MTsN 2 Padangsidimpuan. Qualitative analysis from Miles, Huberman & Saldana was conducted to analyze algebra assignments and student interview results. The results showed that students’ SGP included arithmetic pattern generalization, factual pattern generalization, contextual pattern generalization, and symbolic pattern generalization. High ability students perform symbolic and contextual pattern generalization activities. Medium ability students generalize factual and contextual patterns, and low ability students generalize factual and arithmetic patterns. The contribution of this research is helping students understand the concept of functional material better, increasing students’ generalization abilities, developing students’ abstract thinking skills and helping teachers in designing learning methods.